Specialist training in gastroenterology and liver disease - Long, Richard G.; Scott, Brian B. (Edinburgh Elsevier / Mosby, 2005)
Written for those doctors starting their career in the specialty, this text focuses on diagnostic techniques, treatment and management. It makes use of colour photographs, drawings, lists and tables. Wherever possible, evidence-based treatment options are given and referenced. A list of further reading is also provided.
Keywords: Gastrointestinal diseases -- diagnosis; Gastrointestinal diseases -- therapy; Gastroenterology